(untitled) (Altre Modernità, 2011)
Representations of Oriental woman have evolved through centuries. Pictured as a sexual object by Orientalists in 18th and 19th centuries, or to serve Arab nationalisms (Tunisia, Algeria) in the 20th century, these images have been reconfigured after 9/11 to justify the War on Terror and to serve the Islamist discourse. Therefore, Muslim women have taken advantage of the media attention after 9/11 to get out of this “in-between” and to become the Muslimwoman (re)claiming their bodies, their desires and their sexuality through literature.